Qualidade física do solo após um ciclo de plantas de cobertura - Olbermann, Flavio José Rohden (2021)
Soil management directly infers at the productive potential of crops, and when correctly it provides favorable conditions for root development, which is one of the main objectives of using crop rotation systems, in which, for example, winter cultivation enables the action of roots in improving the physical environment for successor cultures. In this context, the present work evaluated the impact of the use of covercrops on the physical properties of a dystroferric Oxisol, after mechanical soil compaction. The experiment was carried out in a completely randomized design, with six treatments. The treatments consisted of winter crops: (i) Italian ryegrass (Lolium multiflorum); (ii) Mix A (White oats (Avena sativa L), Black oats (Avena strigosa), Rye (Secale cereale) and duckweed (Raphanus sativus L)); (iii) Forage Turnip (Raphanus sativus L.); (iv) Mix B (rye ((Secale cereale); forage pea (Pisum sativum) and turnip var. duckfoot (Raphanus sativus L.)); (v) Black oat (Avena strigosa); and (vi) Wheat (Triticum spp.) During the summer period, all plots were cultivated with soybean. Soil samples were collected at depths of 0-12.5 cm and 12.5-20 cm in two seasons (post cover crops and post-crop. Soybean cover and post-crop.) Soil physical characteristics were taken, such as density (Ds), total porosity (Pt), macroporosity (Mac), microporosity (Mic), mechanical resistance to penetration (RP), and visual evaluation of the structure of the soil. In addition, the grain yield of the soybean crop was subsequently determined. The results indicated improvement in the soil attributes Ds, PT, Mac and Mic, and the Mix A treatment presented the best results when compared to the control (post-compaction), followed by the treatment Mix B, Turnip, Italian ryegrass, Oats and Wheat. The Penetration Resistance Curve (CRP) indicated greater stability of the Mix B treatment, which presented lower RP as a function of volumetric soil moisture, considering the average Ds for the evaluated profile, a fact that occurred inversely in the Oat treatment. When the experiment was evaluated by VESS, most treatments did not differ, with the exception of Turnip, which showed an improvement in the physical soil environment after soybean cultivation. Despite the satisfactory results, in improving the physical soil environment, soybean crop yield did not differ between treatments, and there was no water restriction during its cultivation. It is possible to state that intercropped cover crops have a significant effect on improving soil structure, however.